Understanding the human in stakeholder theory: a phenomenological approach to affect-based learning. Issue 2 (April 2021) - Painter, Mollie; Pérezts, Mar; Deslandes, Ghislain
Despite being one of the most used theories by scholars and practitioners alike, surprisingly little attention has been devoted to how Stakeholder Theory is taught, or to the conception of the human it assumes. In this paper, we address this gap by drawing on the affective phenomenological perspective of Michel Henry, for whom ethics, praxis and even life itself are rooted in affective subjectivity. We argue that bringing back the Latin notion of affectus (as a noun and as a verb) is central to learning about stakeholders by strengthening our understanding of the human – both theoretically and affectively – as it operates within Stakeholder Theory, thereby addressing its anthropological, relational and normative shortcomings. We provide a practical illustration of what this means for learning by reflecting on the affective components of an executive development course on values-driven leadership. We show how the multi-level 'ME-WE-WORLD' framework of this course retrieves the relational normative force that redefines the human from an affective, phenomenological perspective, and enriches the discussion of stakeholders in the classroom. We end by discussing some avenues for future research on how to teach Stakeholder Theory in a more affective and effective way.